Slovak Republic--Joining the EU : A Development Policy Review - World Bank (Washington, DC, 2013)
The Slovak Republic's external current account and fiscal deficits (net of privatization receipts) are unsustainably high (at about 8 percent of GDP in 2002), despite some recent declines. With a capital account surplus of perhaps 20 percent of GDP this year, the Slovak Republic may not find it particularly difficult to finance these deficits, but this favorable situation will not last. Furthermore, through its impact on the real exchange rate, this policy mix is undermining the employability of large segments of the population (particularly those with low skill levels) and will ultimately choke growth (projected at 4 percent for 2002). While much policy attention has gone to stimulating investment, future growth will also depend on raising the employment rate, currently one of the lowest among the Central and East European Countries (CEECs). This report lays out the broad thrust of a policy strategy to bolster the recovery and bring the economy towards convergence with the EU. This strategy consists of three key elements: (a) Continued trade, finance, and enterprise reform to complete the structural transformation of the economy and align it with the EU framework (b) Fiscal consolidation, focusing on cutting back expenditure and stabilizing revenues, while redirecting revenue and expenditure policies to become more fully supportive of growth and employment objectives (c) Labor market reform, directed at enhancing labor market flexibility by relaxing legal provisions on working arrangements (such as part-time work, self-employment, and fixed term contracts), by decentralizing collective bargaining, and discarding the minimum wage as an instrument of incomes policy, and by reforming the social assistance system. The ultimate success of the policy reforms outlined in this report will depend to a great extent on the government's capacity to strengthen the institutional framework in which those policies are conceived, decided upon, and executed. Three priorities have been highlighted: (i) the reform of public expenditure management systems and practices needed to support a growth-oriented fiscal strategy; (ii) the consolidation of the recent decentralization moves as a prerequisite for further devolution, and (iii) a much overdue overhaul of the judiciary system.